Assessment of the results of administrative territorial system and local government reform in Ukraine - Lobunets, Viktoria (Management and Entrepreneurship: Trends of Development, 2019)
Purpose. The topicality of the research is determined by the urgent need to improve the model of public administration, to implement the administrative and territorial reform on the principles of decentralization. The article aims are to study the current state and main problems of the administrative-territorial system reform, to assess the effectiveness of implementing the reform of local self-government and to develop suggestions on improving the efficiency of the united territorial community’s formation and their sustainable development.Design/methodology/approach. The basic principles of the research are historical, systematic and comparative methods, institutional and structural-functional approaches have been used.Findings. The article deals with the analysis of the theoretical basis of decentralization towards changing the administrative territorial structure and carrying out the reform of local self-government. The paper points out the solution of the problems of the administrative territorial reform concerns changing the strategic concept of public administration with an emphasis on  building up a decentralized system of local self-government. Formation of administrative territorial units boundaries, their empowering and financial support are compulsory to achieve the effective result of the reform. Conclusions on the problems and prospects of the administrative territorial reform in Ukraine are made according to the results of the local communities rating. Recommendations ensuring the effectiveness of the administrative-territorial reform implementation and the sustainable development of the united territorial communities are submitted.Research limitations/implications.The concept of decentralization as an effective form of administrative territorial reform, the realization of which will ensure the sustainable development of territorial communities, is proposed. The causes, which level the implementation of administrative territorial reform in Ukraine in the late 90's, are substantiated. The analysis of the main legislative acts ensuring the effectiveness of the local self-government reform and the change of the administrative-territorial system is carried out. The positive influence of the adopted regulatory documents on the dynamics of united territorial communities establishment in Ukraine is proved.Originality/value. It is concluded that the implementation of state power decentralization reform in Ukraine will allow to create a new model of public administration focused on the formation of capable territorial communities capable of solving their own problems independently on the basis of the principles of subsidiarity and financial self-sufficiency.